Design of multiproduct batch plants with units in series including process performance models - Moreno, Marta Susana (2009)
This work deals with the simultaneous optimization of process decision variables and the structure of multiproduct batch plants considering the duplication of units in series to perform a given unit operation. Performance process models allow expressing the size and time factors of the posynomial formulation as a function of the process variables with the highest impact on costs. They are added into the design problem and handled as extra constraints. Structural alternatives for the plant were defined in order to include the duplication of units in series. Thus, the problem is formulated as an optimization problem, using mixed integer nonlinear programming to minimize the total cost of the process, subjected to design specifications. The model application is illustrated with a process for the production of oleoresins. The convenience of including the duplication in series together with process variables in process optimization is tested through the resolution of various problem cases.